Protótipo de uma sonda de perfuração para ser embarcada em um veículo de sensoriamento remoto - Figuerêdo, Edel Mary Quinn de Oliveira (2024)
This work presents the conceptualization of a semi-autonomous probe for environmental exploration and the development of a prototype drilling device designed to assist in soil parameter collection. The project was conceived based on Systems Engineering principles, focusing on a system capable of operating semi-autonomously in areas with desertification potential, such as the Brazilian Semi-Arid Region. The vehicle was described with the minimum requirements to operate as a mobile Data Collection Platform through the intercomparison of data from previously georeferenced areas. The prototype's formulation followed a space systems life cycle, from Phase 0 (conceptualization) to Phase B (final preliminary product). Among its features, the drilling device, an electric drill type, is notable, with its advancement and rotation movements powered by stepper motors. The prototype was assembled, integrated, verified, and tested, with its operation validated according to the adjustment constraints for its full functionality. Through explorations conducted by the vehicle, there is potential support for soil recovery and management projects, promoting sustainable land use and desertification mitigation. This work aligns with Sustainable Development Goal (SDG) 15: Life on Land, focusing on protecting, restoring, and promoting the sustainable use of terrestrial ecosystems and combating desertification.